Facial puffiness caused by dengue fever; two female returning travelers from Laos, and India in the COVID-19 era - Prof Yuji Hirai; Dr. Noriomi Ishibashi (International Journal of Infectious Diseases)
Background: Inaccurate, or delayed diagnosis of dengue cases is associated with increased severity and mortality. The cause of facial puffiness is an allergic reaction, angioedema, blood transfusion reaction, cellulitis, conjunctivitis, drug reactions, and others. Here, we show two female cases with facial puffiness as a rare and tend to overlook manifestation of Dengue fever(DF). Case(s) description: Case 1: A 38-year-old woman was admitted with facial puffiness (FP) with a fever for two days after returning from Luang Prabang in Laos, where she had mosquito bites in June 2023. No rash, myalgia, and arthritis were found at admission. She has no current medical history including medication. She had excessive menstruation bleeding menstruation period earlier for a week. Laboratory evaluation included a White Blood Cell count of 3180/µL, anemia Hb 8.4g/dL, and thrombocytopenia of 8.4 × 104/µL. The serum PCR was positive for the non-structural protein (NS1) of the Dengue virus. On the second day of admission, the rash was available and was expanded from the extremities. Bleeding was resolved on the 5th day, and FP was also resolved on the 7th day of admission.Case 2: A 54-year-old woman, who has already reached menopause, was admitted with a fever and rash for five days after returning from Varanasi in India in November 2023. She has taken sertraline for depression, and Fexofenadine Hydrochloride for hayfever. She also had mosquito bites in Varanasi in India. Her serum PCR was positive for NS1. Although she had no bleeding tendency, FP with a struck marriage ring due to swelling of her fingers was found on the second day of admission. These were resolved on the 8th day of admission. Discussion: A menorrhagia as the first clinical presentation was found in one out of 30 female cases(1). Palpebral edema was found in 20.1% of Dengue fever(2). However, FP was a rare manifestation among adults that was observed commonly in 63% of children(3). FP was associated significantly with dengue hemorrhagic fever (DHF) (p<0.05) (4).FP may be a simple diagnostic cue of DF/DHF among adult returning travelers from pandemic areas that can be extended due to the increasing number of overseas travelers after the COVID-19 era, and global warming. 1. Excessive menstruation bleeding as a presentation of dengue hemorrhagic fever. Arch Gynecol Obstet. 2013;287(6):1271. 2. Mucocutaneous manifestations of Dengue fever. Indian J Dermatol. 2010; 55(1): 79–85. 3. Clinical profile of dengue among children according to revised WHO classification: analysis of a 2012 outbreak from Southern India. Indian J Pediatr. 2015;82:109–13. 4. Demographic and Clinico-Epidemiological Features of Dengue Fever in Faisalabad, Pakistan. PLoS One. 2014; 9(3): e89868.